2020
DOI: 10.17576/jkmjc-2020-3601-23
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Contemporary Security Issues Near Sarawak-Kalimantan Border

Abstract: Stringent border control is one of the methods to secure national security across the world. Securing the border is essential for both economic and political reasons. In Sarawak, border security is one of the most discussed topics on the social media domain when it comes to state security concerns. Due to the porous Sarawak-Kalimantan border, a worrisome number of illegal activities had been recorded. Throughout the years, cases such as illegal crossings, drug syndicates, kidnapping, auto theft, smuggling, inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…These areas tend to be perceived with a significant and constantly changing movement of cross-border activity, presenting unique regional development problems. For example, the borders between Indonesia and Malaysia offer a compelling research opportunity due to the prevailing security concerns, including the illicit trafficking of drugs, human beings, and other commodities, as well as the perceived dangers to the national identities of both nations (Dewantara et al, 2023;Ishikawa, 2018;Jalli & Sualman, 2020;Karulus & Askandar, 2020;Rusdiono & Rochmawati, 2020;Sudagung & Rezasyah, 2020). Nevertheless, these regions also have a peculiarity in more fluid social relationships because it has similarities ranging from the use of the local language and identity of the family as well as emotional relationships as a large family (Awang et al, 2013;Efriani et al, 2020;Sudagung & Chalid, 2016).…”
Section: Public Policy Implementation With the Intersection Of Villag...mentioning
confidence: 99%
See 1 more Smart Citation
“…These areas tend to be perceived with a significant and constantly changing movement of cross-border activity, presenting unique regional development problems. For example, the borders between Indonesia and Malaysia offer a compelling research opportunity due to the prevailing security concerns, including the illicit trafficking of drugs, human beings, and other commodities, as well as the perceived dangers to the national identities of both nations (Dewantara et al, 2023;Ishikawa, 2018;Jalli & Sualman, 2020;Karulus & Askandar, 2020;Rusdiono & Rochmawati, 2020;Sudagung & Rezasyah, 2020). Nevertheless, these regions also have a peculiarity in more fluid social relationships because it has similarities ranging from the use of the local language and identity of the family as well as emotional relationships as a large family (Awang et al, 2013;Efriani et al, 2020;Sudagung & Chalid, 2016).…”
Section: Public Policy Implementation With the Intersection Of Villag...mentioning
confidence: 99%
“…However, other research has shown that the implementation of good governance can also be abused and contraproductive in the case of China and Indonesia (Aminudin, 2019;Wang & Yuan, 2021). Meanwhile, research on the topic of villages in border studies more often focuses on humans or groups of local people as the primary unit of analysis (Wilson & Donnan, 2012) or the nationalism and security policy to harden the border, which positions the national government as the main actors (Jalli & Sualman, 2020;Karulus & Askandar, 2020;Sudagung, 2021). In addition, most of the studies focused on the national policy which impacted the locals compared to the local government's policy (Azizurrahman, 2014;Bangun, 2014;Djuyandi et al, 2023;Madjid & Setiawan, 2021;Sudagung, 2021).…”
Section: Public Policy Implementation With the Intersection Of Villag...mentioning
confidence: 99%